The Law of Torts Including Motar Vehicles Act, consumer Protection Act and Competition Act - Bangia, R K (Faridabad Allahabad Law Agency, 2021)
Law of Torts including compensation under the motor vehicles act and consumer protection laws.
Keywords: Narendra Kumar